Corrección de errores monetarios en el pasivo de deuda financiera. - Acosta Hernandez, Paola Michelle (My University, 2022)
The realization of this work revolves around one of the most important items in business management: financial debt; Specifically, it focuses on those erroneous accounting records derived from the application of an amortization system different from the one initially agreed upon with the financial institution and, said to be said, they are framed by insufficient coordination and communication between the responsible parties involved, facts that in many of cases are not discovered until the execution of a Financial Audit. That is why, the general objective was: Analyze the account of obligations with financial institutions, adjusting the monetary errors detected, for the reasonable presentation of the analyzed component. In this sense, a bibliographical methodology with a quantitative-analytical approach was used, with the support of scientific articles, to proceed to the presentation of a practical case that contributes to a better understanding and analysis of the problem exposed. Finally, the results of the adjustments proposed by the Financial Audit practiced are exposed, with which it is sought to correct the shortcomings detected in pursuit of business welfare, hoping that the research presented will serve as a basis for future studies framed in the line of analysis.
La realización del presente trabajo gira en torno de uno de los rubros más importantes en la gestión empresarial: la deuda financiera; puntualmente, se centra en aquellos registros contables erróneos derivados de la aplicación de un sistema de amortización distinto al inicialmente convenido con la institución financiera y, que dicho sea, se enmarcan a la insuficiente coordinación y comunicación entre los responsables involucrados, hechos que en muchos de los casos, no son descubiertos sino hasta la ejecución de una Auditoría Financiera. Es por ello que, se planteó como objetivo general: Analizar la cuenta de obligaciones con instituciones financieras, ajustando los errores monetarios detectados, para la presentación razonable del componente analizado. En este sentido, se recurrió a una metodología de tipo bibliográfico con enfoque cuantitativo- analítico, para con apoyo en artículos científicos proceder a la presentación de un caso práctico que coadyuve a un mejor entendimiento y análisis de la problemática expuesta. Finalmente, se exponen los resultados de los ajustes propuestos por la Auditoría Financiera practicada, con los que se busca corregir las falencias detectadas en procura del bienestar empresarial, esperando que la investigación presentada sirva de base para futuros estudios enmarcados en la línea de análisis.
Keywords: AUDITORÍA FINANCIERA; DEUDA FINANCIERA; SISTEMAS DE AMORTIZACIÓN; AJUSTES